2020
DOI: 10.1155/2020/1964219
|View full text |Cite|
|
Sign up to set email alerts
|

miR-876 Inhibits EMT and Liver Fibrosis via POSTN to Suppress Metastasis in Hepatocellular Carcinoma

Abstract: Background. The asymptomatic onset, frequent recurrence, and poor prognosis of hepatocellular carcinoma (HCC) prompted us to identify new therapeutic targets or predictive markers of HCC diagnosis or prognosis. Methods. In this study, bioinformatics analysis was used to screen for target miRNAs from the open-access TCGA database. Transwell assays, Western blotting, and qRT-PCR analyses were used to detect cellular functions and gene expression in HCC cells and samples. A nude mouse tumorigenesis model was esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…140 The induction of EMT in HCC significantly promotes metastasis and is mediated by various molecular pathways including miRNAs, SSR2 and ID1. [141][142][143][144] Recent experiments have shed some light on the association between β-catenin signaling and EMT in HCC cells. The trans-activation response DNA-binding protein of 43 kDa (TDP-43) is suggested to suppress translation of GSK-3β to induce Wnt/β-catenin axis.…”
Section: Beta-catenin Cancer Proliferation and Migrationmentioning
confidence: 99%
“…140 The induction of EMT in HCC significantly promotes metastasis and is mediated by various molecular pathways including miRNAs, SSR2 and ID1. [141][142][143][144] Recent experiments have shed some light on the association between β-catenin signaling and EMT in HCC cells. The trans-activation response DNA-binding protein of 43 kDa (TDP-43) is suggested to suppress translation of GSK-3β to induce Wnt/β-catenin axis.…”
Section: Beta-catenin Cancer Proliferation and Migrationmentioning
confidence: 99%
“…The co-expression molecules of SOX2 and SOX10 were really small, so the roles of these three SOX family molecules in HCC may need to be explored separately. In addition, the top 10 hub genes POSTN, BGN, MMP2, THBS2, CD34, ESR1, VEGFC, AEBP1, CLDN5, and LOXL1 seem to be related with cancer stemness (such as cancer-associated fibroblasts [ 55 ], EMT process [ 56 ], tumor immune infiltration [ 57 ], and metastasis [ 58 ]). In conclusion, the function of SOX family on HCC may link with these cancer stemness-related proteins, and these proteins may have a potential to be biomarkers or therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-876 inhibited HCC EMT and fibrosis by targeting POSTN, thereby affecting HCC progression and prognosis. MiR-876 and POSTN may be useful therapeutic targets or prognostic markers for HCC [47]. Another study demonstrated that the combined assessment of POSTN protein overexpression and microvascular invasion in HCC is associated with poor prognosis and can be used as a good prognostic marker for HCC [48].…”
Section: Liver and Biliary System-related Malignanciesmentioning
confidence: 99%